The logic of writing and the organization of society. - Goody, Jack (Studies in literacy, family, culture, and the state, 1986)
Counter This book assesses the impact of writing on human societies, both in the Ancient Near East and in contemporary Africa, and highlights some general features of social systems that have been influenced by this major change in the mode of communication. Such features are central to any attempt at the theoretical definition of human society and such constituent phenomena as religious and legal systems, and in this study Professor Goody explores the role of a specific mechanism, the introduction of writing and the development of a written tradition, in the explanation of some important social differences and similarities. Goody argues that a shift of emphasis from productive to certain communicative processes is essential to account adequately for major changes in human societies. Whilst there have been previous discussions of the effect of literacy upon social organisation, no study has hitherto presented the general synthesis developed here -- Présentation de l'éditeur.